PRAGMATIC INTENTION IN LITERARY DISCOURSE (Academicia Globe: Inderscience Research, 2022)
The pragmatic study of literary discourse also takes into account the issues of impact and perception as two sides of communication. They ensure an entire communication process only when used jointly. As "two sides of the coin," impact and perception are inextricably linked and interdependent. The concept of pragmatic aim plays an important role in examining the effectiveness of impact and perception. The addresser's purposeful intention to exert influence on the addressee with the goal of causing some reconstruction in his world picture is referred to as pragmatic intention. We can explore pragmatic aim in literary discourse in this essay.